Water types and their functional role: Perception, myth and fact - Diana Sunardi (Indonesian Nutrition Association, 2020)
There are many incorrect perceptions in public as well, and we have to educate people to be more aware about what they buy and drink for their daily fluid intake, also to believe information only from the trusted source.